Travel and Leisure Activities, Motivation and Behavior of Young Bangladeshi Tourists - Md. Nafi, Shohel; Ahmed, Tanvir (European Scientific Journal, ESJ, 2018)
The purpose of this study is to find the motivational factors and travelling patterns of young tourists at home and abroad. Leisure activity and vacations aren’t considered as luxury anymore. In their busy life Vacation is one of the core elements of mental support system. Despite an increasing interest in the market size of young travelers, economic potential and their desire to travel, relatively little is known about their travel motivation, expectation and intention. Therefore, this study aims to provide insights of young Bangladeshi travelers’ lifestyles and travel intentions. This study mainly focuses on the behavioral and motivational aspects of the tourists when they choose a vacation and in a vacation. The survey questionnaire is divided into three sectors; first part focuses on the demographic characteristics of the respondents, second part focuses on the motivational and behavioral aspects of young tourists; third part describes the travel motivation and behavior of outbound tourists. The sample of 200 young tourists has been selected based on Simple Random Sampling method to collect data. The survey data are being analyzed in a descriptive manner. SPSS 20.0 software has been used to analyze the primary data. This study used frequency analysis, table and chart to analysis data. The study suggests that the way of leisure spending have been altering over the period of time. The vibrant young travelers of Bangladesh are bringing their constructive influence in this business for the last decade with their ever changing test and demand being constantly updated with worldwide trend.